Correlation of lipid profile with blood pressure in apparently healthy Sudanese individuals in Northern State, Sudan - Taha, Elmutaz H.; Awad, Kamal M.; Osman, Makawi A. A. (International Journal of Research in Medical Sciences, 2025)
Background: To assess the value of lipid profile on apparently healthy adult Sudanese based on the blood pressure values in Dongola town in the northern state. This study aims to correlate the lipid profile with the blood pressure to figure out their association with cardiometabolic disorders Methods: a cross-sectional prospective study was carried out from January 2018 to November 2018 in Dongola on apparently healthy adult Sudanese. Results: in this study 164 individuals have been tested, out of them 117 (71.34%) were females and males 47 (28.65%) respectively. Most of the study group were normal weight, females 63 (38.41%) and males 20 (12.19%) respectively. The arterial blood pressure values showed a significant positive correlation to both BMI and lipid profile (p-value≤0.05). Also, results revealed that fasting blood glucose has a strong positive correlation with lipid profile HDL and TG (p value≤0.05), TC and LDL (p value≥0.01). Conclusions: Our results concluded that patients with hypertension are more likely than normotensive patients to exhibit dyslipidemia, including elevated TC, LDL, TG and reduced HDL cholesterol levels. Our results suggest that elevated BP may predict certain disturbances in lipoprotein metabolism.